The Dark Sides of Immigrants in Laila Lalami’s Hope and Other Dangerous Pursuits - Wati, Dhiviya Syares; Malik, Khansa Humaira; Sulistiawati, Yuni; Tayem, Nada (Muslim English Literature, 2024)
This study focuses on the impact of immigration on immigrants, especially Muslim women or Muslimah, by engaging with a postcolonial study working within the framework of gender and immigration and using a close textual analysis. The researchers use a qualitative research method to reveal the reasons Moroccan women decide to illegally immigrate to Spain in Laila Lalami’s Hope and Other Dangerous Pursuits (2005), investigated to reveal what it means to be Muslimah immigrants crossing the Moroccan sea to live in Spain. The data collected is in the form of quotes, narratives, and discourse from the primary text and the secondary sources. The storyline of this novel revolves around unlawful (illegal) immigrants from Morocco to Spain. This novel is about the struggles of four Moroccan immigrants who have no place and space to live either in their homeland or in the host land. In this study, the theme of 'immigrant Muslimah' leads researchers to the conclusion that the novel uses the dark sides of being immigrants who have the desire to reject white officers and politicians who tend to blame immigrant Muslimah as a problem instead of the victim of global transitional capitalism and ‘patriarchism’.